2011
DOI: 10.1007/s00256-011-1171-x
|View full text |Cite
|
Sign up to set email alerts
|

T2 star relaxation times for assessment of articular cartilage at 3 T: a feasibility study

Abstract: Within this feasibility study, both T2 and T2* relaxation parameters demonstrated a similar response in the assessment of articular cartilage and cartilage repair tissue. The potential advantages of T2*-mapping of cartilage include faster imaging times and the opportunity for 3D acquisitions, thereby providing greater spatial resolution and complete coverage of the articular surface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
145
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 20 publications
5
145
1
Order By: Relevance
“…The gradient echo T2*WI sequence is likely to fill the gap between MRI findings and clinical knee instability of physical examination. The T2*WI sequence can reportedly detect subtle changes in tissue biochemical composition, and can clearly visualize slight structural changes such as microdamage in the ligament, cartilage, or meniscus [12,18,19]. Interestingly, T2* relaxation time has been reported to show a significant negative correlation with collagen content and positive correlations with both water and proteoglycan contents [20], suggesting that T2*WI probes water mobility within the collagen network, and allows more sensitive assessment of graft integrity after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The gradient echo T2*WI sequence is likely to fill the gap between MRI findings and clinical knee instability of physical examination. The T2*WI sequence can reportedly detect subtle changes in tissue biochemical composition, and can clearly visualize slight structural changes such as microdamage in the ligament, cartilage, or meniscus [12,18,19]. Interestingly, T2* relaxation time has been reported to show a significant negative correlation with collagen content and positive correlations with both water and proteoglycan contents [20], suggesting that T2*WI probes water mobility within the collagen network, and allows more sensitive assessment of graft integrity after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…31 With the goal of early detection to monitor clinical endpoints and to develop therapeutic interventions, quantitative MRI measurements sensitive to cartilage matrix composition should be evaluated as they are complementary to morphological assessments. 11,3640 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the potential of dGEMRIC and T2* mapping in knee and hip joint cartilage [4,6,7,9,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, despite one dGEMRIC study that reports the contrast dynamics in hyaline and fibrous cartilage after intra-articular gadolinium injection in cadaveric shoulders [31], to the best of our knowledge, dGEMRIC and T2* mapping have not yet been performed in the shoulder joint.…”
Section: Introductionmentioning
confidence: 91%